Mg doped SnO2 electron transport layer enhances planar all inorganic perovskite solar cells efficiency - Qixin Chen; Zhongchen Bai; Xu Wang; Xishun Peng; Xinghua Li; Cheng Zuo; Zhengping Zhang (iScience)
Summary: The electron transport layer (ETL) plays a crucial role in fabricating efficient and stable planar perovskite solar cells (PSCs). Among the various alternatives to TiO2 for electron transport layers (ETLs), tin oxide (SnO2) has emerged as a highly promising candidate due to its outstanding potential. However, improvements in SnO2 materials remain necessary due to inherent limitations, such as low conductivity, high energy barrier, and interfacial defects. In this study, Mg2+ ions were introduced into SnO2 to substitute Sn sites, leading to an increase in the open-circuit voltage (Voc) of PSCs, and consequently enhancing overall device efficiency. With a Mg doping concentration of 3.0%, the Voc and power conversion efficiency (PCE) of the solar cell reached 1.540 V and 7.17%, respectively. The incorporation of Mg2+ ions into SnO2 presents an effective method to improve the performance of SnO2 ETL in PSCs while utilizing more environmentally friendly solvents.